Representing Australian aboriginal music and dance 1930-1970 - Harris, Amanda, 1976-; Foster, Shannon (D'harawal); Onus, Tiriki; Simpson, Nardi (New York : Bloomsbury Academic, 2020)
"A performance-centered history of the Australian "assimilation" era that centralizes auditory worlds and audio-visual evidence of Aboriginal music and dance"--
Includes bibliographical references and index.
Keywords: Aboriginal Australians -- Music -- History and criticism; Dance, Aboriginal Australian -- History; Music -- Australia -- 20th century -- History and criticism